Abundância e padrão de distribuição de Rhinemys rufipes (SPIX, 1824), Chelidae, em uma floresta de terra firme na Amazônia Central - Sanchez, Diego Emanuel Arruda (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
Rhinemys rufipes (SPIX, 1824) is a chelid turtle with cryptic and nightly behavior that lives in small streams in terra-firme rainforests in the Western Amazon. A population of this species occurs in the Adolpho Ducke Forest Reserve - RFAD, a 10000 ha terra-firme forest area near Manaus, Amazonas state, Brazil. In the 1990s a population of this species that occurs in the RFAD was the object of a series of studies about its biology and ecology. Presently the reserve is still in good conservation state, but is becoming increasingly isolated from continuous forest areas due to the urban expansion of Manaus. The scope of this study was to evaluate the abundance, occupancy pattern and dispersal capacity of R. rufipes in the RFAD, considering that isolated populations of long-lived organisms such as chelonians are particularly more susceptible to adverse effects due to habitat isolation. I also compared my estimates with estimates generated for this population in the 1990s. Throughout 2007 I carried out four mark-recapture sessions in 5-km transects of four different streams in the RFAD. I estimated adult abundance for each sampled transect, and extrapolated the abundance estimate for all streams in the RFAD. I also evaluated the relation between five habitat variables and presenceabsence data of R. rufipes at 240 trapping points. There was high heterogeneity in capture probability among transects. Abundance estimates varied between 42 and 57 adult animals among transects. The occurrence of males and females was not related to any habitat variable measured, but the occurrence of gravid females was negatively related to stream width. The number of individuals estimated for the entire reserve varied between 420 and 1100 individuals, well below the abundance estimate of 2500 individuals established in the 1990s.
Keywords: Quelônios; Rhinemys rufipes; Habitat de tartaruga